Telehealth cancer-related fatigue clinic model for cancer survivors: a pilot randomised controlled trial protocol (the T-CRF trial) - Jane Turner; Nicolas H Hart; Patsy Yates; Laisa Teleni; Joanne F Aitken; Lee Jones; Steven M McPhail; Rahul Ladwa; Fiona Crawford-Williams; Raymond J Chan; Mark B Pinkham; Elizabeth P Pinkham; et al. (BMJ Open)
Introduction Cancer-related fatigue (CRF) is one of the most common and debilitating adverse effects of cancer and its treatment reported by cancer survivors. Physical activity, psychological interventions and management of concurrent symptoms have been shown to be effective in alleviating CRF. This pilot randomised controlled trial (RCT) will determine the feasibility of a telehealth CRF clinic intervention (T-CRF) to implement evidence-based strategies and assess the impact of the intervention on CRF and other clinical factors in comparison to usual care.Methods and analysis A parallel-arm (intervention vs usual care) pilot RCT will be conducted at the Princess Alexandra Hospital in Queensland, Australia. Sixty cancer survivors aged 18 years and over, who report moderate or severe fatigue on the Brief Fatigue Inventory and meet other study criteria will be recruited. Participants will be randomised (1:1) to receive the T-CRF intervention or usual care (ie, specialist-led care, with a fatigue information booklet). The intervention is a 24-week programme of three telehealth nurse-led consultations and a personalised CRF management plan. The primary objective of this pilot RCT is to determine intervention feasibility, with a secondary objective to determine preliminary clinical efficacy. Feasibility outcomes include the identification of recruitment methods; recruitment rate and uptake; attrition; adherence; fidelity; apathy; and intervention functionality, acceptability and satisfaction. Clinical and resource use outcomes include cancer survivor fatigue, symptom burden, level of physical activity, productivity loss, hospital resource utilisation and carer’s fatigue and productivity loss. Descriptive statistics will be used to report on feasibility and process-related elements additional to clinical and resource outcomes.Ethics and dissemination This trial is prospectively registered (ACTRN12620001334998). The study protocol has been approved by the Metro South Health and Hospital Services Human Research Ethics Committee (MSHHS HREC/2020/QMS/63495). Findings will be disseminated through peer-reviewed publications, national and international conferences and seminars or workshops.Trial registration number Australian New Zealand Clinical Trials Registry ID: ACTRN12620001334998; Pre-results. Trial Version: Version 1.1. Last updated 10 December 2020.